The Influence of Good Corporate Governance Mechanisms and Profit Management (Empirical Study on Agricultural Sector Companies Listed on the Indonesia Stock Exchange in 2015-2018) - Siswanti, Febi; Hizazi, Achmad; Wijaya, Rico (Faculty of Economics and Business Universitas Jambi, 2023)
This study is entitled